To Develop Piezoelectric based Acoustic Microfluidic Mixer - Tharun Kumar Reddy, Pelleti (VNU Journal of Science: Mathematics - Physics, 2022)
The main of this research is to solve the problems of the mixing of fluids in microchannels. The aim is to improve the mixing efficiency of the microchannel by employing the piezoelectric actuator. The objectives of the project are to, producing ZnO (Zinc Oxide) thin films, preparing the microchannel with desired dimensions and examining the mixing efficiency of the microchannel by employing the piezoelectric actuator. The ZnO nanoparticles were produced by the coprecipitation method, and the purity and phase were checked by using the XRD method, the ZnO thin films were produced by the Ultrasonic Spray pyrolysis, the thickness of the thin films was determined by using the Eddy current method, the mixing efficiency was measured by powering the piezoelectric actuator by AC source. The size of the nanoparticles is 53.88 nm, The thickness of the ZnO-coated copper thin films is 102 µm, the mixing efficiency can be increased up to 93.47% with the help of an active source of energy Piezoelectric actuator. The mixing efficiency is further increased by increasing the length of the microchannel, increasing the cross-sectional area of the microchannel, in the maximum voltage kept at 5 V because of the limitation of the piezoelectric actuator.